Performance Comparison of CFC12, HCR12 and HCR12+LFS as Refrigerants - Damitri, Nila; Soekardi, C; Prasetyo, B. T; Sarwono, Sarwono; Kafiuddin, Kafiuddin; Suwono, A; Pasek, A. D; Tandian, N. P (Mesin, 1999)
Additional concern about warming of the global environment through the greenhouse effect has necessitated selection of compounds with shorter atmospheric lifetimes and higher energy efficiencies as substitute reï¬igerants for Heating, Air Conditioning, and refrigerating equipment.Several substitute compounds of the hidrocarbon were identified by similarities in normal boiling points and corresponding saturated vapor pressure characteristics. Sample quantities were obtained from ITB (Two sample corresponds with CFCIZ named Hycool HCRI2 and Hycool HCR12+LFS). Performance comparisons among these refrigerants are performed utilizing Air Conditioning System test facility in Laboratory for Thermodynamics, Engines and Propulsion System (LIMP â BPP Teknologi). The results show that these alternatives refrigerants exhibit better performance than CFC I 2 at the predetermined operating conditions.